PENGOLAHAN SLUDGE DENGAN PROSES BIOLOGI ANAEROBIK - Ikbal M.Eng (Jurnal Teknologi Lingkungan, 2006)
Mixed sludge generated from wastewater treatment plant increases annually.Organic content as COD of the mixed sludge is about 20.000mg/l, which isconsidered to be high-strength wastewater. Due to the sludge have high watercontent, it cannot self-burn. In addition, in many industries, there is not enoughland for landfill. For this reason, an experiment of anaerobic treatment wasconducted to investigate the degradation of organic materials in the mixedsludge. The result shows that high degradation efficiency of organic sludge of 90, 70 and 50% was achieved at organic loading rate of 0,7; 1,4 and 2,1 g/l/drespectively. The degradation efficiency decreased drastically when the organicloading rate increased up to 2.8 g/l/d. During the experiment, gas evolution ratewas low due to low organic content of the sludge.